Tanfiidz Barnaamij Jaulah Al ‘Arabiyah Fii Ma’had Al Ittihad Al Islaami Sampang Madura ‘Ala Dhoui Nadzhoriyyati Georg R. Terry - Fini Adila Kurnia; Robiatul Laili Maulidiyah; Zakiya Arifa (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2024)
The aims of this research are (1) to determine the orientation of the implementation of Jaulah 'Arabiyah, (2) to determine the steps for implementing the Jaulah 'Arabiyah Program, (3) to determine the factors needed in implementing the Jaulah 'Arabiyah Program. This research method is qualitative, using field research, interviews, and observation data collection techniques. The analysis techniques used are data reduction, data presentation, and conclusion. Meanwhile, the results of the research are (1) Arabic language skills are a measure of Jaulah ‘Arabiyah program success, (2) steps for implementing the program Jaulah ‘Arabiyah: group division, determining musyrifah, art performances, and charity bazaars, (3) factors that influence the implementation of the Jaulah ‘Arabiyah: Leadership, attitudes and morals, communication, incentives, supervision, discipline.